Scaling limits and aging for a representation of the Bouchaud and Dean model on a k-level tree - Delgado, Andrea Karina Hernández (2024)
We define a process in the space of càdlàg functions from \\R_+ to R_+^k which is described using a family of jump functions constructed explicitly and we prove a result that establishes the weak convergence of the process as a consequence of the almost sure convergence of the family of jump functions. We then apply it to a representation of the trap model on a k-level tree introduced by Bouchaud and Dean to obtain scaling limit results.